2006
DOI: 10.1002/cyto.b.20143
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the expression of glycosylphosphatidylinositol‐anchored proteins during the maturation of different hematopoietic cell compartments of normal bone marrow

Abstract: Conclusion: Overall, these results provide a detailed map GPI-AP expression during normal hematopoietic differentiation, which could serve as a basis for the identification and characterization of changes occurring in PNH. q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 19 publications
2
49
0
1
Order By: Relevance
“…The presence of cells with CD59 loss/low expression was not related to immature myeloid cells in the peripheral blood, a finding in keeping with the observation by Hernandez-Campo et al that there is no significant change in CD59 expression throughout myeloid maturation. 31 We back-traced the cells with CD59 loss/low expression and found, at least in some cases, that these cells clustered in the junction between monocytes and granulocytes ( Figure 2A3). It is noteworthy that monocytes often exhibit significantly dimmer expression of CD59 than granulocytes, 17 , were more prominent in CMML or RAEB in their series 19 and concluded that the detection of large numbers of PNH + cells was associated with a poor prognosis.…”
Section: Cd66bmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of cells with CD59 loss/low expression was not related to immature myeloid cells in the peripheral blood, a finding in keeping with the observation by Hernandez-Campo et al that there is no significant change in CD59 expression throughout myeloid maturation. 31 We back-traced the cells with CD59 loss/low expression and found, at least in some cases, that these cells clustered in the junction between monocytes and granulocytes ( Figure 2A3). It is noteworthy that monocytes often exhibit significantly dimmer expression of CD59 than granulocytes, 17 , were more prominent in CMML or RAEB in their series 19 and concluded that the detection of large numbers of PNH + cells was associated with a poor prognosis.…”
Section: Cd66bmentioning
confidence: 97%
“…It has been shown that the expression of GPI-anchored proteins varies throughout neutrophil and monocyte maturation. 17,31,32 The level of CD55 expression is low in early myeloid precursors until the intermediate stages of maturation, and increases in bands and granulocytes. The expression of CD16 is detectable on metamyelocytes, reaching highest levels on bands/mature neutrophils.…”
Section: Cd66bmentioning
confidence: 99%
“…This is a fluorochrome-conjugated inactive variant of the bacterially derived channel-forming protein aerolysin, which binds specifically to GPI-anchors. FLAER may offer significant advantages as a reagent for PNH testing; in contrast with antibodies against many of the GPI-linked antigens normally studied (25,27,28), its binding is less sensitive to the maturational stage of the cells. FLAER can also be used in multicolor combinations with monoclonal antibodies to GPI-linked and non-GPI antigens for the detection of PNH clones (29).…”
Section: Diagnosis Of Pnhmentioning
confidence: 99%
“…Similarly, granulocytes from aged samples (>48-h old) may show altered FSC/SSC scatter characteristics due to poor viability and can also show increased nonspecific binding of antibodies. Another potential pitfall with granulocyte analysis is the presence of immature forms that have significantly weaker expression of some GPI-linked antigens when compared with more mature forms (25,28). In patients with granulocytopenia and relatively high proportions of eosinophils, it may be difficult to construct a pure granulocyte gate unless appropriate markers are used in multicolor analysis.…”
Section: Additional Factors Affecting Interpretationmentioning
confidence: 99%
“…Pig-a mutation can be measured rapidly using small samples of peripheral blood and flow cytometry, which accounts for the popularity of this assay (Dobrovolsky et al, 2010). Pig-a encodes a protein involved in the synthesis of glycosylphosphatidylinositol (GPI) anchors that link a specific subset of proteins to the cell surface, including the antigens CD59, CD55, CD24, and CD48 (Kawagoe et al, 1994;Hernandez-Campo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%